A signaling theory approach to relationship recovery. (30th June 2020) - Kharouf, Hunsi; Lund, Donald J.; Krallman, Alexandra; Pullig, Chris
Abstract : Purpose: Drawing on signaling theory, the purpose of this study is to investigate the effects of the strength and framing of firm signals sent to repair relationships following relationship violations. Design/methodology/approach: Three 2 × 2 scenario-based experiments (total n = 527) manipulate signal strength × violation type (Study 1); signal frame × violation type (Study 2); and signal strength × brand familiarity (Study 3) to examine their dynamic impacts on relationship recovery efforts. Findings: Stronger signals are more effective at relationship repair and are especially important following integrity (vs competence) violations. Signals framed as customer gains (vs firm costs) lead to more favorable relationship outcomes. Finally, brands that are less (vs more) familiar see greater benefits from strong signals. Research limitations/implications: The three experiments were scenario-based, which may not replicate real-life behavior or capture participants' actual emotions following a violation, thus future research should extend into real-world recovery efforts. Practical implications: Managers should send strong signals (communicating the level of resources invested in the recovery efforts) framed as benefits to the customer, rather than costs to the firm. Strong signals are especially important when brand familiarity is low or an integrity violation has occurred. Originality/value: This is the first research to directly apply signaling theory to the relationship recovery process and contributes to theory by examining the role of signal strength; framing of the signal as a customer gain vs firm cost; and the interplay of signal strength and brand familiarity on the relationship recovery effort.